Increasing the Knowledge of Church Citizens through Education on the Importance of Unity of Service as a Foundation for Spiritual Growth - Maahury, Yane Rosmawati; Banga, Berthin S.; Simangungsong, Yohana R. (Universitas Lambung Mangkurat, 2025)
Some congregation members consider church service the responsibility of the Pastor, the Congregation Council, the Working Board of the Congregation Council, the Church Holidays Committee, or specific groups due to a lack of understanding and awareness of the concept and importance of service unity. Through community service activities at the GKI Syalom Siba Congregation, Sentani, lecturers from the Theology Department of STAKPN Sentani showed dedication to answering the congregation's needs. As a foundation for the spiritual development of the GKI Syalom Siba congregation, Sentani, this community service activity aims to enlighten the congregation on the importance of service unity. The community service activities were conducted using a lecture and question-and-answer format. The congregation of GKI Syalom Siba participated actively and enthusiastically during the activity. The lecture and question-and-answer methods were effective, and the delivery of simple and easy-to-understand materials contributed to the success of this community service activity. Thus, within the framework of congregational unity at GKI Syalom Siba, Sentani, this activity not only increases the intellectual acumen of the congregation but also becomes the basis for its spiritual development. The community service activities not only enrich the knowledge of the congregation but also provide a solid foundation for the spiritual growth of the Pastor, the Elemental Management Board, and the Congregation, totalling fifty people in the context of the unity of ministry at the GKI Syalom Siba Congregation, Sentani.